Gray sabbath : Jesus people USA, evangelical left, and the evolution of Christian Rock - Young, Shawn David (New York : Columbia University Press, 2015)
Formed in 1972, Jesus People USA is an evangelical Christian community that fundamentally transformed the American Christian music industry and the practice of American evangelicalism, which continues to evolve under its influence. In this fascinating ethnographic study, Shawn David Young replays not only the growth and influence of the group over the past three decades but also the left-leaning politics it developed that continue to serve as a catalyst for change. Jesus People USA established a still-thriving Christian commune in downtown Chicago and a ground-breaking music festival that red.
Introduction -- The largest American commune -- The blessing and curse of community -- Big shoulders, big history: why Chicago? -- Theology, politics, and culture -- The Christian woodstock: -- The future: ex-members, second generation, and social dynamics -- Conclusion.
Description based upon print version of record.
Includes bibliographical references and index.
Master record variable field(s) change: 050
Keywords: Jesus People -- United States; Evangelicalism -- Illinois -- Chicago -- History -- 20th century; Christian rock music -- United States; RELIGION / Christianity / History; Christian rock music; Evangelicalism; Jesus People; Illinois -- Chicago; United States; 1900-1999; Electronic books; Electronic books; History